Herlyn-Werner-Wunderlich syndrome: a challenging diagnosis - Leite,Sara Dias (2022)
Abstract Herlyn-Werner-Wunderlich syndrome (HWW) is a rare congenital anomaly of the female urogenital tract, characterized by the triad of bicorporeal uterus, obstructed hemivagina and ipsilateral renal agenesis. The most common symptoms are pelvic pain, dysmenorrhea and an abdominal mass. Prompt surgical treatment is advisable. If not immediately possible, medical treatment should be initiated to induce amenorrhea. We describe a case of HWW with chronic pelvic pain and mild dysmenorrhea. The ultrasound revealed uterine duplication and a retro-uterine mass contiguous to the cervix. Magnetic resonance imaging (MRI) confirmed a genital tract anomaly. The patient was medicated with continuous oral estroprogestative and was proposed to surgery.